IT Service Desks: Management & Standards - Asari, Nadia Shazrin (2009)
This is a study of best practices in managing an IT organization, which focuses on the Service Desk. It takes into account the several available industry best practice framework such as ITIL and CoBIT. It concludes with a practical guide to implementing IT Service Management within an IT organization